Tarjuma-yi Kitāb al-milal wal-niḥal - Shahrastānī, ʿAbd al-Karīm (Miras Maktoob, ISBN: 9789004365452., 2019)
Muḥammad b. ʿAbd al-Karīm Shahrastānī was born in 479/1086-7 in Shahristān in today's Turkmenistan. After his basic education he went to Nishapur, then a major centre of learning. Afterwards, he taught for some years at the Niẓāmiyya academy in Baghdad. Returning to Khurāsān around 514/1120, he became a staff member at the chancellery of the Saljuq ruler, Sanjar (d. 552/1157), entertaining close relations with him. At some point Shahrastānī returned to his hometown, although it is not known why or when, dying there in 548/1153. His influential history of religions and sects, which also includes an account of Greek and Islamic philosophy, is one of his best known works. Until recently only two Persian translations of it were known: one by Afḍal al-Dīn Turka-yi Iṣfahānī dated 843/1449-50, and an improved edition of it by Muṣṭafā b. Khāliqdād, dated 1021/1612. The anonymous translation published here is much older and may even date from Shahrastānī's own lifetime.